2009
DOI: 10.1128/jcm.01236-09
|View full text |Cite
|
Sign up to set email alerts
|

First Neisseria gonorrhoeae Genotyping Analysis in France: Identification of a Strain Cluster with Reduced Susceptibility to Ceftriaxone

Abstract: isolates. The major STs identified in France were previously described elsewhere. However, two newly described STs, ST1479 and ST1987, had only been found in France until now. ST1479 was characterized by a multipleresistance phenotype, whereas ST1987 presented a susceptibility phenotype. Moreover, among the predominant French STs, ST225, which had already been described in many countries, comprised isolates (14/16) resistant to ciprofloxacin and with reduced susceptibility to ceftriaxone. Thus, the surveillanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
0
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 20 publications
4
18
0
4
Order By: Relevance
“…For example, ST1407, which contains a penA mosaic allele, has been found to cause decreased susceptibility to ESCs in many countries worldwide [22]. Moreover, ST292 has been previously found in other European countries such as Sweden [22], France [23], and Scotland [24]. In general, the NG-MAST results also showed that the strains circulating in Norway were heterogeneous; 72 NG-MAST STs, 37 not previously described, were found among 114 isolates.…”
Section: Discussionmentioning
confidence: 59%
“…For example, ST1407, which contains a penA mosaic allele, has been found to cause decreased susceptibility to ESCs in many countries worldwide [22]. Moreover, ST292 has been previously found in other European countries such as Sweden [22], France [23], and Scotland [24]. In general, the NG-MAST results also showed that the strains circulating in Norway were heterogeneous; 72 NG-MAST STs, 37 not previously described, were found among 114 isolates.…”
Section: Discussionmentioning
confidence: 59%
“…(2,9,10). However, the method has also been used, as it is here, to compare gonococcal isolates recovered from different years across whole countries (7,13,14,16,26). The method has some drawbacks for this purpose, as variant STs that differ at either porB or tbpB and then at both loci will rapidly be generated.…”
Section: Overview Of Qrng Isolates Recovered Between 1997 and 2007mentioning
confidence: 99%
“…Based on this two-locus-combined profile, the isolates were equally assigned as ST225, which indicates a shared ancestral origin for these isolates. The ST225 seems to be an emerging multi-resistant clone that has been recently identified in many countries such as Australia (Todd et al 2007), Scotland (Palmer et al 2008), France (Monfort et al 2009), Portugal (Florindo et al 2010) and Greece (Mavroidi et al 2011). In fact, ST225 was the most prevalent ST in Scotland and France and has been reported as the second major genotype among QRNG isolates that were collected between 1997-2007 in Greece.…”
mentioning
confidence: 99%
“…In addition, ST225 was recently associated with reduced susceptibility to ceftriaxone (Monfort et al 2009, Whiley et al 2010. Until now, the CLSI (2010b) did not stipuUntil now, the CLSI (2010b) did not stipuUntil now, the CLSI (2010b) did not stipudid not stipulate MIC values to reduced susceptibility or resistance to ceftriaxone.…”
mentioning
confidence: 99%